Psychosocial Characterization of HIV Clients with Potential to be Change Agents for HIV Prevention in Uganda - Tumwine, Christopher; Mbona Tumwesigye, Nazarius; Mugyenyi, Peter; Wagner, Glenn (Journal of Clinical Research In HIV AIDS And Prevention, 2012)
New research suggests that people living with HIV have the potential to be strong advocates for HIV prevention by passing on HIV prevention messages within their social networks. However, there is a paucity of research into the nature and prevalence of HIV prevention behaviours engaged in by HIV clients, and the psychosocial correlates of such advocacy, which are the goals of this analysis. We examined engagement in HIV prevention advocacy among 602 new HIV clients at two clinics in Uganda. Eighty nine percent reported encouraging others to get tested for HIV, 79% told people they know to use condoms when they have sex, and 61% reported discussing HIV more generally with friends and family. A client was classified as fully engaged in HIV prevention advocacy if they reported engaging in all three of the measured HIV prevention advocacy behaviors. In the bivariate analysis, being from the rural study site (p<0.001), higher levels of HIV disclosure to friends (p<0.001), greater hopefulness (p<0.001), and lower levels of depression (p<0.001) and internalized HIV stigma (p<0.001) were associated with full engagement in HIV prevention advocacy. In the multivariate analysis, being from the rural study site (OR=5.461, 95% CI=3.11-9.61), lower levels of internalized HIV stigma (OR=0.524, 95% CI=0.39-0.70) and higher levels of HIV status disclosure to friends (OR=2.040, 95% CI=1.23-3.38) remained significantly associated with full engagement in prevention advocacy. These data suggest that psychosocial adjustment and functioning may play a key role in empowering HIV clients to be advocates for prevention.
Keywords: psychosocial; HIV/AIDS; change agents; prevention with positives; disclosure; stigma; Uganda